Fundamentals of Corporate Finance : Ready Notes for use with - Ross, Stephen A. (Irwin, 1993)
Introduction to corporate Finance. Financial Statements, Taxes, and Cash Flow. Working with Financial Statements. Long-Term financial Planning and Growth. Firts Principles of Valuation. Valuing of Stocks and Bonds. Issuing Securities to the public...